Reinforcement of pimobendan with guideline-directed medical therapy may reduce the rehospitalization rates in patients with heart failure: retrospective cohort study - Yoshiki Iwade; Yoshiaki Kubota; Daisuke Hayashi; Takuya Nishino; Yukihiro Watanabe; Katsuhito Kato; Shuhei Tara; Yuya Ise; Kuniya Asai (BMC, 2024)
Abstract Background Pimobendan reportedly improves the subjective symptoms of heart failure. However, evidence of improved prognosis is lacking. This study aimed to determine whether reinforcing guideline-directed medical therapy (GDMT) improved rehospitalization rates for worsening heart failure in patients administered pimobendan. Methods A total of 175 patients with heart failure who were urgently admitted to our hospital for worsening heart failure and who received pimobendan between January 2015 and February 2022 were included. Of the 175 patients, 44 were excluded because of in-hospital death at the time of pimobendan induction. The remaining 131 patients were divided into two groups, the reduced ejection fraction (rEF) (n = 93) and non-rEF (n = 38) groups, and further divided into the GDMT-reinforced and non-reinforced groups. Results In patients with rEF, the rate of rehospitalization for heart failure was significantly lower in the GDMT-reinforced group than in the non-reinforced group (log-rank test, P = .04). However, the same trend was not observed in the non-rEF group. Conclusions Reinforcing GDMT may reduce the heart failure rehospitalization rate in patients with pimobendan administration and rEF. However, multicenter collaborative research is needed. Trial registration IRB Approval by the Nippon Medical School Hospital Ethics Committee B-2021-433 (April 10, 2023).